Construção de conhecimentos e currículos in-venta-dos com as mídias nos cotidianos de uma escola pública de ensino médio - Almeida, Edivan Carneiro de (2014)
This research deals with the experiences/performed by a group of students and the teacher-Coordinator of the Project Communication, Interaction and Learning, developed at the State School, Aristides Cedraz de Oliveira, in Ichu town, in the hinterland of Bahia. At this school I have worked as teacher for almost two decades. Going through traces-fragments of those experiences and experiencing affections and expressions, we aim to understand some possibilities for the accomplishment of the construction of practices-expressions of knowledge and creating of a curriculum, operated by students and teacher in/of /with/school High School quotidian. We also aim to understand the collective processes (and) trading/producing of meanings/signification, of empowerment and emancipation through its knowledge-making powers, affecting their lives and the development of the curriculum, which we understand to be practice based on their reflections upon their quotidian at school, in opposition to subversion/strategies, attempts to prescription-determination taken by the educational policy-makers. To do so, we have used the video mapping as an instrument to outline the strategies of appropriation-bricolage and creative activities developed by the students and the teacher in order to use media and languages in the production of information in Communication Project. We have realized that the experience pointed to important opportunities to build knowledge and appropriation of the media language resources through the production of texts, written and oral information, brought to the school and community daily, through school radiobroadcast, the blog and the printed bulletin. These productions-trials have been carried out and affected students‟ lives, leading to empowerment and emancipation in their political participation in their school and external community as well as interfering in their choices and in their ways to see/think/act, extending their possibilities of insertion, interference-transformation and participation in society. The narratives of those experiences through workshops and videos, also allowed us to understand that the activities developed in the project have caused strong changes in the official strict-prescriptive curriculum and enhanced the creation of a unique curriculum, by creating other ways to see/think/act in the construction of knowledge/thoughts/sentiments, affections and negotiations of meanings, producing experiences inside and outside school. Thus, one expects to see a shared curriculum, full of life, cheerful, animated, renewed and fulfilled with meanings produced by the High School students.